3D hollow MXene (Ti3C2)/reduced graphene oxide hybrid nanospheres for high-performance Li-ion storage. Issue 42 (8th October 2021) - Guo, Miao; Zhong, Shulin; Xu, Tian; Huang, Yuqin; Xia, Guanglin; Zhang, Tengfei; Yu, Xuebin
Abstract : Transition metal carbon/nitrogen compound (MXene) materials have been regarded as promising candidates for lithium-ion storage. Abstract : Transition metal carbon/nitrogen compound (MXene) materials have been regarded as promising candidates for lithium-ion storage. However, two-dimensional (2D) MXenes with abundant surface functional groups easily accumulate spontaneously, which significantly reduces their specific surface area and further limits their lithium-ion storage properties. In this study, uniform three-dimensional (3D) hollow MXene nanospheres with an average diameter of < 300 nm were first synthesized via a template method, which used positively charged polystyrene (PS) as a template. Furthermore, reduced graphene oxide (rGO) was introduced to wrap the hollow MXene nanospheres to form hybrid MXene@rGO nanospheres. The 3D structure of the composite can not only increase the specific surface area of the material and prevent the accumulation of sheets, but also reduce the effect of volume expansion upon cycling. Meanwhile, the layer spacing between rGO and MXene sheets is only 0.26 nm, which further promotes charge exchange at the interface, so as to improve the electrochemical kinetic performance of the material. Thus, the hollow MXene@rGO nanospheres exhibited excellent rate properties as anodes for lithium-ion batteries, providing a high capacity of 241.5 mA h g −1 after 5000 cycles at 10 A g −1 . It is demonstrated that 3D MXene@rGO nanospheres are a promising anode material for high-rate lithium-ion batteries.